Interactions and social identity of support teachers: An ethnographic study of the marginalisation in the inclusive school - Milani Marin, Laura Emma; Jacomuzzi, Alessandra Cecilia (Frontiers in Education, 2022)
Educational personnel are seen as agents of change toward inclusive schools. This research aims to examine the daily-based interactions through which inclusion is experienced by support teachers and how their social identity is constructed within a secondary school in a northern Italy province. The theoretical basis of this research is formed by the conceptual contributions of social identity approach and symbolic interactionism to understand self-categorization and identification processes, through the narratives of actors. An ethnographic design was implemented, with 4-month participant observation and 20 semi-structured interviews of long duration as the main data collection techniques. Fieldnotes and interviews transcriptions were inductively analysed through a thematic approach to grounded theorising. Results show a school community in which there is a strong hierarchical relationship among main and support teachers, where support teachers experience strong feelings of inferiority and marginalisation, since they have entered school. These school interactions are also shaped by the school culture and management. However, support teachers have a potential avant-garde role as agents of change in the inclusion process. Future research should target this aspect to investigate best inclusive practices.